Study of Arrhythmias in Acute Myocardial Infarction - S, Nagabhushana; kumar GK, Ranjith; Ranganatha, M; Virupakshappa, Virupakshappa (International Journal of Medical Research and Review, 2015)
Background: Acute Coronary Syndrome (ACS) represents a Global epidemic. There is not much documented evidence regarding the profile of arrhythmias in the present population of Shimoga. Hence the purpose of this study is to evaluate the incidence and profile of cardiac Arrhythmias in AMI in the first week of hospitalization in a tertiary care hospital in shimoga, karnataka. Material and Methods: 100 patients of Acute Myocardial Infarction (AMI) admitted to ICCU of Mc Gann Hospital from April 2015 to June 2015 were studied. The first electrocardiogram (ECG) was recorded at the earliest after admission, subsequently at four hourly interval on first day, daily for the duration of stay and as & when needed, cardiac enzymes and 2D echocardiography were done to confirm MI. Result: The mean age was 52.914  13.19 years with male to female ratio being 2.9:1. Incidence of arrhythmias was 89%, majority (67%) of arrhythmias occurred during first 24 hours. Sinus tachycardia (48%), ventricular premature beats (VPCs) (24%), Sinus bradycardia (22%) and atrial premature complexes (15%) were common arrhythmias encountered in study. Atrioventricular blocks (93.4%) were more common in inferior wall infarctions. Arrhythmias were documented in 90.91% of anterior wall MIs, 83.33% of inferior wall MIs and 100% of combined (anterior and inferior) MIs. Conclusion: Our observations confirmed the differences in the occurrence of arrhythmias in different setup and locality and need for individualization of management protocol in different setup.